2019
DOI: 10.3390/ani9010013
|View full text |Cite
|
Sign up to set email alerts
|

Garlic (Allium Sativum) Supplementation Improves Respiratory Health but Has Increased Risk of Lower Hematologic Values in Horses

Abstract: Simple SummaryThe hypotheses of this study were that garlic supplementation may help to clear mucus in the airways, but also causes declining hematologic values in prolonged feeding. The results show that long-term supplementation of dried garlic on the level of 32 mg/kg BW improved respiratory health in terms of reduced amount of tracheal symptoms and accumulation of tracheal exudates. However, the garlic supplemented horses showed slightly declining hemoglobin (Hb), hematocrit (HcT) and red blood cells (RBC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 28 publications
0
5
0
3
Order By: Relevance
“…Posiblemente los contrastes antes mencionados, se deba a diferencias en protocolos de sanidad, exposición a enfermedades, altitud de la región y alimentación. Siendo este último, probablemente el causante de cambios hematológicos en equinos (19).…”
Section: Resultsunclassified
“…Posiblemente los contrastes antes mencionados, se deba a diferencias en protocolos de sanidad, exposición a enfermedades, altitud de la región y alimentación. Siendo este último, probablemente el causante de cambios hematológicos en equinos (19).…”
Section: Resultsunclassified
“…Multiple studies have documented its biological effects: antioxidant, anti-inflammatory, immunomodulatory, antibiotic, bacteriostatic, a n t i f u n ga l , a nt i -v i ra l , a n t i h e l m i n t h i c , antithrombic, hypotensive, hypoglycemic, and hypercholesterolemic, as well as anti-influenza B, herpes simplex, and coxsackievirus anti-viral activity [69][70] . Some studies reported that Garlic molecules could modulate cytokine expression in lipopolysaccharide-activated human blood and inhibit NF-êB from which show its immunemodulatory effect is evident 71 .…”
Section: Rasona[allium Sativum]garlicmentioning
confidence: 99%
“…It is also involved in activating macrophages, promoting immunoglobulins 71 , and reducing polymorphonuclear cells' migration through endothelial cell layers 72 . Some studies have observed that it involved inhibiting the fabrication of NO and prostaglandin-E2, suppresses inducible form of NO synthase and COX-2 expression, decreases the production of inflammatory cytokines like TNF-a, interleukin 6, and interferon ã [70][71][72] . Some other finding has supported that involved to improve lung function in smokers, 73 and reduce tracheal exudates in horses 73 .…”
Section: Rasona[allium Sativum]garlicmentioning
confidence: 99%
“…Son yıllarda, sarımsakta bazı immunmodülatör etkili proteinlerin varlığı saptanmış olmasına rağmen, bunların özellikleri henüz ortaya konulamamıştır [31]. Atlar üzerinde yapılan bir çalışmada yemlerle birlikte 32 mg/kg dozda uzun süreli kuru Allium sativum takviyesinin, trakeal hastalıkların semptomlarını ve trakeal eksüdat birikimini azalttığını, ancak hayvanlarda hemoglobin, eritrosit ve hematokrit değerlerde azalmanın meydana geldiği bildirilmiştir [32] [36]. Yine köpeklerde yapılan bir çalışmada Aleo vera ve Coriandrum sativum'un antiobezite ve antidiabetik etkileri incelenmiş, köpeklere 5 haftalık periyotta ilk hafta kontrol diyeti, 2 hafta bitkisel preparatlardan oluşan diyet ve son 2 hafta arınma diyeti uygulanmıştır.…”
Section: Allium Sativumunclassified